Organizational Transformation of Regional Secretariats through a Learning Organization Approach: A Systematic Review from an Educational Management Perspective - Parizal Parizal; Rizky Firnanda; Tukini Rahmawati (Vokatek: Jurnal Pengabdian Masyarakat, 2026)
Public sector organizations require continuous transformation to respond to technological advances, bureaucratic complexity, and increasing demands for effective public services. This study aims to analyze the transformation of Regional Secretariats through a learning organization approach from an educational management perspective. This study employed a Systematic Literature Review (SLR) by searching the literature through Google Scholar, Scopus, and other relevant academic databases. Following the identification, screening, eligibility, and inclusion stages based on predetermined criteria, 10 studies were selected for the final synthesis. The findings reveal that learning organization principles support organizational transformation through four key dimensions: human resource development, learning culture strengthening, knowledge management, and adaptive capacity improvement. From an educational management perspective, these principles contribute to the development of sustainable learning systems through effective planning, implementation, supervision, and evaluation. The study implies that integrating learning organization concepts with educational management practices can strengthen the capacity, innovation, and adaptability of Regional Secretariats in achieving more responsive and sustainable public governance